24=m2-n2

Rewrite the equation as m2-n2=24.

m2-n2=24

Add n2 to both sides of the equation.

m2=24+n2

Take the square root of both sides of the equation to eliminate the exponent on the left side.

m=±24+n2

First, use the positive value of the ± to find the first solution.

m=24+n2

Next, use the negative value of the ± to find the second solution.

m=-24+n2

The complete solution is the result of both the positive and negative portions of the solution.

m=24+n2,-24+n2

m=24+n2,-24+n2

Solve for m 24=m^2-n^2